Penggunaan Digital Marketing terhadap Peningkatan Brand Awareness PT Produk Zilla Akademi Indonesia - Hayyina Rahma; Nanik Hariyana (Cv. Utility Project Solution, 2023)
The utilization of digital marketing has become a crucial strategy for expanding reach and building brand awareness. This research employed a qualitative descriptive research method with a case study. The research findings indicate that B2B collaborations significantly contribute to increasing brand awareness by enabling the company to expand its brand reach, build trust, and attract new audiences. The role of mentors, such as Yoel Sumitro has also proven effective in boosting brand awareness through the association with their own reputation and authority. In addition, the use of Instagram social media can help brands by increasing their exposure, driving audience engagement, reinforcing their brand identity through visually appealing content, and increasing awareness through targeted advertising. Proven to be effective in raising awareness. To increase brand awareness, PT Produk Zilla Akademi Indonesia can focus on B2B collaboration with relevant companies, take advantage of mentor roles such as Yoel Sumitro, and optimize the use of Instagram social media with attractive content strategies and targeted paid advertising. By combining these strategies, PT Produk Zilla was able to achieve a significant increase in brand awareness in the creative education and training industry. By combining B2B collaboration strategies, mentorship, and the use of Instagram social media, PT Produk Zilla Akademi Indonesia can achieve significant improvements in brand awareness and optimize their marketing efforts in the creative education and training industry.